The clone wars. Volume 2 - Edginton, Ian; Pugh, Steve (Star Wars legends epic collection, 2018)
The Clone Wars rage on! And the fighting is fierce as General Kenobi and his first lieutenant, Anakin Skywalker, brace for the Battle of Jabiim! Facing attacks from both the Republic and the locals, can Anakin and his 'Padawan Pack' hold the rain-soaked planet - or will they face a washout? Then, Skywalker finds himself behind enemy lines alongside a Tusken Raider-turned-Jedi! But where is Obi-Wan? Perhaps Dark Jedi Asaji Ventress has the answer! Meanwhile, Senator Bail Organa is plagued by pirates, and Quinlan Vos goes undercover within Count Dooku's inner circle. All that, plus Mace Windu unleashed!